Location Of Suitable Sites For Wind Farms Using Tools Of Spatial Information. - Shamshad, A; Bawadi, M A; Wan Husin, WMA (2003)
The rapid increase in the global population and fast depleting reserves of fossils fuel and increasing environmental pollution have encouraged the search for alternative source of environmental friendly renewable energy.